Barriers to accessing HIV and sexual health services among gay men in Tasmania, Australia. Issue 2 (3rd April 2019) - Lea, Toby; Anning, Matt; Wagner, Sabine; Owen, Louise; Howes, Faline; Holt, Martin
Abstract: We examined barriers to accessing HIV and sexual health services among gay and bisexual men (GBM) in Tasmania, Australia, using in-depth interviews. Most participants were satisfied with the care they had received at public sexual health services. Barriers included the limited number of services, concerns about anonymity and privacy in small communities, difficulties accessing services via a general practitioner, and perceived stigma and discrimination. Improving the accessibility and availability of HIV and sexual health services in Tasmania is crucial to promote the engagement of GBM, which could be achieved via combined efforts of government services and community organizations.